Digitization of Hizib Nahdlatul Wathan by TGKH. Muhammad Zainuddin Abdul Madjid Based on the OPF Flipbook - Hariman Bahtiar; Muhammad Djamaluddin; L.M. Samsu (IAIC Publishing, 2020)
TGKH. Muhammad Zainuddin Abdul Madjid is one of the charismatic figures and scholars who came from Lombok's island. He has produced many works to serve as a guide for the students and congregation who bought him from leading. Most of Maulana Shaykh's results still use conventional media in the form of paper. With these conventional media, mostly with frequent use or improper placement, the media can become damaged. The use of technology to maintain and preserve great charismatic figures and scholars such as TGKH Muhammad Zainuddin Abdul Madjid is very important. One of the works of business is Hizib Nahdlatul Wathan, hizib, which is a collection of regular and selected prayers with a direct target. The Hizb Nahdlatul Wathan book's creation in the digital form helps students and congregations to read business works from anywhere. One of the advantages of the Hizb Nahdlatul Wathan ebook is that this ebook uses the OPF flipbook format so that when we open it it is as if we are opening the original book. Besides providing the text, this ebook also includes sound facilities for reading the lyrics in the book. So in addition to reading, we can again listen to the sound of the chanting of the book's lyrics at once.